In Search for Anti-Aging Strategy: Can We Rejuvenate Our Aging Stem Cells? - Anna Meiliana; Nurrani Mustika Dewi; Andi Wijaya (The Indonesian Biomedical Journal, 2015)
BACKGROUND: Recent evidence suggested that we grow old partly because of our stem cells grow old as a result of mechanisms that suppress the development of cancer over a lifetime. We believe that a further, more precise mechanistic understanding of this process will be required before this knowledge can be translated into human anti-aging therapies.CONTENT: A diminished capacity to maintain tissue homeostasis is a central physiological characteristic of aging. As stem cells regulate tissue homeostasis, depletion of stem cell reserves and/or diminished stem cell function have been postulated to contribute to aging. It has further been suggested that accumulated DNA damage could be a principal mechanism underlying age-dependent stem cell decline. It is interesting that many of the rejuvenating interventions act on the stem cell compartments, perhaps reflecting shared genetic and biochemical pathways controlling stem cell function and longevity. Strategy to slow down the aging processes is based on caloric restriction refers to a dietary regimen low in calories but without undernutrition. Sirtuin (SIRT)1 and 3, increases longevity by mimicking the beneficial effects of caloric restriction. SIRT3 regulates stress-responsive mitochondrial homeostasis, and more importantly, SIRT3 upregulation rejuvenates aged stem cells in tissues. Resveratrol (3,5,4’-trihydroxystilbene), a natural polyphenol found in grapes and wine, was the most powerful natural activator of SIRT1. In fact, resveratrol treatment has been demonstrated to rescue adult stem cell decline, slow down bodyweight loss, improve trabecular bone structure and mineral density, and significantly extend lifespan.SUMMARY: Tissue-specific stem cells persist throughout the entire lifespan to repair and maintain tissues, but their self-renewal and differentiation potential become dysregulated with aging. Given that adult stem cells are thought to be central to tissue maintenance and organismal survival, SIRT3 may promote organismal longevity by maintaining the integrity of tissue-speciic stem cells.KEYWORDS: rejuvenation, aging, stem cell, DNA damage, sirtuin activator